Immunogenicity of Ribonucleic Acid Preparations Obtained from Salmonella typhimurium - Venneman, Martin R. (1970)
Mice immunized with purified whole-cell ribonucleic acid (RNA), RNA from the bacterial “particulate” fraction, and ribosome-associated RNA obtained from Salmonella typhimurium were found to be resistant to subsequent challenge infection with virulent salmonellae. Chemically, the immunogenic nucleic acid fractions contained from 1 to 3% “contaminant” material defined (based on the mean of 19 different preparations) as protein (0.24%), deoxyribonucleic acid (0.43%), methyl pentose (0.64%), hexose (1.58%), and undefined carbohydrate (0.76%). Heptoses and lipoidal material were not detectable in any of the immunogenic preparations examined. Physically, the nucleic acid preparations, after analytical ultracentrifugation, exhibited three boundaries similar to those reported elsewhere in comparable systems: 4 to 5S, 16S, and 23S. An evaluation of the immunity induced by the ribosome-associated RNA established that the immune response was (i) comparable to that induced 15 days postimmunization with live salmonellae and by ribosomal vaccines, but greater at 30 days postimmunization than that in mice immunized with attenuated salmonellae; (ii) dependent on the quantity of immunogen administered; (iii) dependent on the size of the infective inocula; (iv) inhibited at 15 but not at 30 days postimmunization when the immunogenic nucleic acid preparations were incorporated into Freund's incomplete adjuvant, (v) reduced or lost by dialysis in relatively high or low immunizing doses, respectively; and (vi) unaffected by enzymatic treatment of the preparations with trypsin, deoxyribonuclease, Pronase plus pancreatic ribonuclease, or pancreatic ribonuclease alone. The possible mode of action of ribosome-associated RNA in inducing an immune response to subsequent challenge infection with the homologous organism is discussed.